Media Agenda and Voters’ Behavior in Khyber Pakhtunkhawa (A Case Study of General Elections-2013) - Imran Ahmed; Dr. Muhammad Shahzad; Ali Hassan (Journal of Peace, Development and Communication, 2021)
This study investigates the relationship between voters’ exposure to media agenda in terms of exposure of different political contents by the all media sources and its consequent impacts on their voting behavior. Data collection has been made with the help of face to face interviews method from 150 respondents (75 male and 75 female registered voters) belonging to province Khber Pakhtunkhwa of Pakistan. Findings explored that in KPK during 2013 general elections, PTI (Pakistan Tahreek-e-Insaf) is perceived as the most favored party over other political parties. Findings further revealed that respondents preferred social media most influential to acquire political information followed by electronic media, social interaction and print media. To measure the change induced through exposure to mass media, findings revealed that majority of respondents opted very much role of media that strengthen the notion of powerful effects of media on voting behavior. The findings further illustrated that to produce change in voting behavior, Facebook identified as most influential source among other social media applications, Talk Shows from TV contents, columns in newspapers’ contents and news in radio shown the as most influential in this regard. Respondents’ dependency to alter vote choice found less dependent on TV followed by newspapers and almost negligible for radio whereas social media performed a noteworthy role in this context.